PEMANFAATAN PLATFORM MERDEKA MENGAJAR SEBAGAI UPAYA MENINGKATKAN KUALITAS PEMBELAJARAN GURU DI PROVINSI BANTEN - Setiariny, Endang; Sanmarwi, Sodiyah (LPMP Provinsi DKI Jakarta, 2024)
Effective learning quality is one of the important factors in improving student learning outcomes. The Merdeka Mengajar (PMM) Platform, developed by the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, provides digital solutions to support teacher competency development through various innovative features. This article aims to analyze the use of PMM by teachers as an effort to improve the quality of learning. This study uses a descriptive qualitative method through interviews, observations, and documentation studies of elementary and secondary school teachers. The results of the study indicate that PMM has a positive impact on improving teachers' abilities in designing learning, student evaluation, and continuous professional development. This study also bases its findings on constructivist learning theory, educational technology, and the concept of continuous professional development.